Teaching Speaking Techniques For The Seventh Grade Students Of Smp N 1 Weru In The Academic Year Of 2016/2017 - Robbani, Aini Endu, Dr. Anam Sutopo, Mauly Halwat Hikmat, Ph.D (2017)
Technique is classroom practices done by the teacher when presenting a language program. It is believed that the teacher in teaching learning activities using some techniques be successful and give a good result. The type of this research is descriptive qualitative research. The primary data are the answers to the document and field notes of interview and observation result. This research focuses on the questions problems statement such as: the techniques, the purposes, the problems faced by the teachers, the solutions of the teachers, the teachers' roles and students' roles. The techniques used by the Teacher at SMP N 1 Weru in teaching speaking activities are role play, discussion and games. The purpose of the teachers' uses these techniques are to improve enthusiasm and interest of the students' in speaking English. The teacher does not only teach the students but also gave motivations to the students in the classroom. The roles of teachers at SMPN 1 Weru are controller, observer, corrector, prompter, resource and assessor. The result of students' roles in speaking activities at SMP N 1 Weru such as: The learner is monitor and evaluator for his or her own progress.